The Calderón Projector for an elliptic operator in divergence form - Sanmartino, Marcela (2001)
The Calderon Projector, is one of the most important tools in the study of boundary value problems for elliptic operators. Its construction is well known for elliptic operators with C∞ coefficients on C∞ domains and even for the Laplacian operator on C1 domains. The aim of this article is to extend the results for the Laplacian case to elliptic operators in divergence form with Lipschitz coefficients on C1 domains.